Estudo das alterações cariotípicas, do rearranjo gênico BCR/ABL e do cromossomo 20 em leucemias - Goloni, Cristina B. V. [UNESP] (Elsevier, 2001)
Leukemia is a genetic disease from a noncontrolled abnormal process of the hematopoietic cells' differentiation and proliferation. Some alterations of structure and number of chromosomes have been well and specifically observed in leukemia. The detection of these alterations is highly significant in providing the patients' diagnosis, prognosis and treatment as well as the understanding of the genetic bases of this disease. The purpose of this work is to study some chromosomal alterations in peripheral blood and/or bone marrow in patients with different leukemia types by means of conventional cytogenetic techniques, and also to investigate the presence of BCR/ABL gene rearrangement and some alterations in chromosome 20 by the FISH technique. Samples of peripheral blood and/or bone marrow of 28 patients, who were not under chemoor radio-therapeutic treatment, were studied: 15 with CML, 11 with AML and 2 with ALL. The alteration most frequent was t(9;22) in the CML, whose presence or absence was related to a good or bad prognosis, respectively. A case of AMI showed inv(16)(p13q22), related to a good prognosis. Some alterations not reported previously in the literature were found, such as the trisomy in chromosome 2 associated to chromosome Ph showing some disease progress in one of the CML cases and t(5;16)(q13;q22) in an AML patient. One of the cases was submitted to an allogeneic hone marrow transplant. The monitoring after the 23 rd day of transplant, detected 95% of the donor cells suggesting the procedure had succeeded. Two patients, an AMI and the other ALL, showed trisomy of chromosome 20 in the neoplastic cells. The results showed the importance of the cytogenetic analysis in relation to leukemia, its direct benefits to the patients and the biological mechanisms involved in this disease. They also allowed the introduction in the Genetic Service of FAMERP techniques to obtain the bone marrow metaphases and the FISH technique.
Study of karyotypic alterations, BCR/ABL gene rearrangement of the chromosome 20 in leukemia patients